UPAYA BNP2TKI DALAM MENCEGAH TERJADINYA TRAFFICKING IN PERSONS TENAGA KERJA INDONESIA DI ARAB SAUDI - Khairunnisa, Sastya Anggun; Susitianingsih, Hermini; Pattipeilohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
High population density in Indonesia constricts the job opportunitiesfor Indonesian and gives impacts such as poverty and unemployment.These constricted job opportunities make the people in Indonesia seekfor a job abroad to fulfill their needs. The transmission of Indonesianlabour to Saudi Arabia is increasing every year, triggering the labourissues in Indonesia, such as many forms of harassment that entirelyconducive for human trafficking. This research aims to find outIndonesia’s efforts to prevent trafficking in person of Indonesianlabour in Saudi Arabia through the National Agency for ThePlacement and Protection of Indonesian Labour, as one of the bodiesdirectly responsible to president. To answer the problem, the theory ofinternational migration, the theory of human trafficking, humanrights, and theory of cooperation in the paradigm of liberalism, areused in this research. This research uses qualitative method withdescriptive-analytical type by using literature reviews and interviewsresearch technique. The result shows that the efforts done by theBNP2TKI in preventing trafficking in person of Indonesian labour arenot optimal yet, where there are still many weaknesses and constraintsin preventing human trafficking.